Variations in micronutrient concentrations and retentions in fufu made from yellow-fleshed cassava as a function of genotype and processing methods - Williams-Ngegba, Martha Shirley Epiphaneia; Onabanjo, Oluseye Olusegun; Anthony, Nyahabeh Mariama; Alamu, Emmanuel Oladeji; Maziya-Dixon, Busie; Oguntona, Emmanuel Babatunde (Frontiers in Nutrition, 2024)
Introduction The biofortification of staple foods such as cassava is one of the technological breakthroughs in the nutritional improvement of foods. Fufu is one of the fermented cassava products produced and consumed in major West African countries, including Sierra Leone, and the majority of the processes involved in its production have direct and indirect effects on its properties. This study looked at how the concentration and retention of micronutrients in yellow-fleshed cassava fufu varied depending on genotype and processing method. Methods Six yellow-fleshed cassava root genotypes (TMS-070557, TMS-011371, TMS-011412, TMS-011663, TMS-083724, TMS-083774) and one white (TME 419 as a control) were processed into fufu using both conventional (oven and sun-dried) and traditional (bowl and river) methods. The Statistical Analysis System (SAS) version 9.4 was used to analyze data using means, percentages, analysis of variance and means separated by least significant differences (LSD). Results and Discussion In the modified traditional river method, raw and cooked fufu samples had significantly higher β-carotene concentrations and true retention (TR) percentages (11.06 g/g (46.77%) and 4.54 g/g (16.94%), respectively) than other genotypes (p < 0.0001). Modified traditional fufu processing methods increased total β-carotene concentrations, while raw roots showed a significant decrease in total carotenoid and β-carotene concentrations, regardless of genotype or processing method. Sun-drying was the most effective method, with significantly higher concentrations and TR percentages of iron (10.01 mg/kg, 18.02%) and zinc (11.49 mg/kg, 40.64%) in raw and cooked fufu samples. Genotype TMS-083724 outperformed both conventional fufu processing methods, displaying a significant total carotenoid concentration and true retention percentage. Finally, this study found that the concentrations and percentages of TR of micronutrients varied depending on the processing method and genotype. It is recommended that a modified traditional river fufu processing method be further developed and improved in order to maximize provitamin A carotenoids, concentrations, and percentage TR.